Synthesis of Benzo[a]naphtho[2,3-c]xanthones from 2-styrylchromones - Tomé, Sara (2012)
2-Styrylchromones, a small group of natural occurring chromones vinylogues of flavones (2-phenylchromones) have been ex tensively studied (both by synthesis and transformations)111 due to their known important biological activities. 121 Following our interest in 2-styrylchromones and exploiting its reactivity as synthons in the preparation of other type of compounds, we studied their reactivity as dienophile in the Diels-Alder reaction with ortho-benzoquinodimethanesY1 Another field of interest of our research group is the chemistry of xanthones. 141 This class of oxygen-containing heterocyclic compounds is also associated with a broad spectrum of pharmacological propertiesY1 The interesting biological profile of benzoxanthones 161 is an example that the tricyclic core of xanthones may represent a promising key in medicinal chemistry. In this communication we present a route towards the synthesis of benzo[a]naphtho[2,3-c]xanthones from 2-styrylchromones. Here we discuss the experimental procedures and reaction mechanisms of the Diels-Alder transformation of 2-styrylchromone 1 into the oxidized cycloadduct 3 and its subsequent photoinduced electrocyclization and oxidation that gave access to the desired benzo[a] naphtho[2,3- c]xanthone 4.